Patient experience with healthcare services among older adults with serious mental illness compared to the general older population. (November 2017) - Fortuna, Karen L; Lohman, Matthew C; Batsis, John A; DiNapoli, Elizabeth A; DiMilia, Peter R; Bruce, Martha L; Bartels, Stephen J
Objective: To compare patient experience with healthcare services and providers among older patients (≥50 years old) with and without serious mental illness. Methods: Using secondary data from the Medical Expenditures Panel Survey from 2003 through 2013, we compared adults aged 50 years and older with schizophrenia spectrum disorder ( n = 106), mood disorders (i.e., major depressive disorder and bipolar disorder) ( n = 419), and no serious mental illness ( n = 34, 921). Results: Older adults with schizophrenia spectrum disorder reported significantly worse provider communication than older adults without serious mental illness. Older adults with mood disorders reported the greatest barriers to shared decision-making and the greatest difficulty accessing services. Conclusions: Our results highlight the need to improve the patient experience of older adults with serious mental illness. Addressing provider communication, shared decision-making, and access to care among this vulnerable group of older adults may impact clinical outcomes and costs. Future research examining the extent to which improving the patient experience may improve health outcomes and enhance treatment for this highly vulnerable older group is warranted.